Effect Of Service Quality And Product Quality Of Electronic-Based Applications (Bsi Mobile) On Customer Satisfaction At Pt Bank Syariah Indonesia Tbk KC Bengkulu S. Parman 2 - Agustatulim Agustatulim; Wagini Wagini; Suswati Nasution (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
Service quality and product quality based on electronic applications (BSI Mobile) are expected to affect customer satisfaction at PT. Bank Syariah Indonesia TBK KC Bengkulu S. Parman 2, where the BSI Mobile product was created to facilitate customers in transacting, so that customers wherever and whenever they are can transact and manage their finances easily. The purpose of this study was to find the effect of service quality and product quality on customer satisfaction at PT. Bank Syariah Indonesia KC Bengkulu S. Parman 2. The sample in this study was 100 customers who had used BSI Mobile products. Collecting data using a questionnaire and the analysis method used is multiple linear regression, validity test, reliability test, simultaneous f test, coefficient of determination and hypothesis testing using t test. The results of the regression equation are Y=3.522+0.455X1+ 0.319X2 b0= indicating the number 3.522, which means that if all the independent variables, namely service quality and product quality, are constant, the number of the dependent variable shows the number 35.2% as the result value of the dependent variable so that it can determine customer satisfaction. .0.455X1 = value 0.455 and 0.319X2 = value 0.319 is a value that indicates that service quality (X1) and product quality (X2) have a positive effect on customer satisfaction (Y), so that each additional 1% of respondents' responses about service quality and quality the product will affect the variable (Y) namely customer satisfaction with a value of 4.55% and 3.19%. The hypothesis in this study is accepted because the value of t arithmetic > t table, the independent variable (Service Quality and Product Quality) partially affects the dependent variable (Customer Satisfaction). Keywords: Service quality, Product quality, BSI Mobile, Customer Satisfaction